2020
DOI: 10.1177/1756287220904806
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics and musculoskeletal symptoms in surgeons performing endoscopic procedures for benign prostatic hyperplasia

Abstract: Background and purpose: Benign prostatic hyperplasia (BPH) is the most common urologic disorder affecting older men, necessitating medical or surgical intervention. Limited data exists regarding the effect these surgeries have on the endourologist’s musculoskeletal system following the surgery because of the required difficult posture, prolonged procedures, repetitive movements, and the settings of an adjustable visual display terminal workstation. The aim of our study was to survey the prevalence and possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The novices completed the tasks more quickly and with a lower workload when using robotic manipulation, whereas the experts showed the opposite trend. The learning rate in all groups was greater for robotic manipulation (21.02% on average) than for conventional manipulation (13.75%) [32,33] .…”
Section: Easyendo Robotic Endoscopy System (Easyuretero)mentioning
confidence: 85%
See 1 more Smart Citation
“…The novices completed the tasks more quickly and with a lower workload when using robotic manipulation, whereas the experts showed the opposite trend. The learning rate in all groups was greater for robotic manipulation (21.02% on average) than for conventional manipulation (13.75%) [32,33] .…”
Section: Easyendo Robotic Endoscopy System (Easyuretero)mentioning
confidence: 85%
“…This robotic catheter system was modified and equipped with a fiber endoscope and a customized ureteral catheter to perform ureteroscopy with the commercial master device Omega 3 (Force Dimension, Switzerland), although the existing drawbacks of inappropriate control mode and inadequate working range partially contributed to the termination and eventual failure of this project [22,26,27] . Kwon et al [32,33] 2022 easyEndo robotic endoscopy system (EasyUretero) Phantom None…”
Section: Sensai-magellan Systemmentioning
confidence: 99%
“…Omar et al showed normal weight and overweight participants are more commonly affected in work-related musculoskeletal disorders among surgeons [39]. Singh et al also stated in their research those normal-weight participants are most vulnerable to work-related musculoskeletal disorders [40].…”
Section: Discussionmentioning
confidence: 98%
“…Suboptimal ergonomics significantly impacts urologists' health, contributing to musculoskeletal injuries, burn‐out and early retirement. Endoscopic surgery is maximally burdensome 22 . Although the effect of laser goggles on surgical ergonomics has not been directly evaluated, experience tells us that ill‐fitting eyewear frequently requiring readjustment is likely to negatively impact surgeons, affecting positioning, comfort and visibility.…”
Section: Implications Of Current Laser Safety Requirementsmentioning
confidence: 99%
“…Endoscopic surgery is maximally burdensome. 22 Although the effect of laser goggles on surgical ergonomics has not been directly evaluated, experience tells us that ill-fitting eyewear frequently requiring readjustment is likely to negatively impact surgeons, affecting positioning, comfort and visibility. Operative ergonomics has been identified as a key target to improve career longevity and reduce burnout in the United States, where urology workforce shortages loom.…”
Section: Implications Of Current Laser Safety Requirementsmentioning
confidence: 99%